2020
DOI: 10.1152/ajpheart.00399.2020
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of serum and glucocorticoid-regulated kinase 1 exacerbates brain injury and neurological deficits after cardiac arrest

Abstract: Cardiopulmonary arrest (CA) is the leading cause of death and disability in the United States. CA-induced brain injury is influenced by multi-factorial processes, including reduced cerebral blood flow (hypoperfusion) and neuroinflammation, which can lead to neuronal cell death and functional deficits. We have identified serum and glucocorticoid-regulated kinase-1 (SGK1) as a new target in brain ischemia previously described in the heart, liver, and kidneys (i.e. diabetes and hypertension). Our data suggest bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…GSK-650394 has been validated in in vitro models to attenuate cerebral ischemia-reperfusion injury. [ 31 33 ] Related studies have shown that GSK-650394 exhibits antitumor activity in established breast cancer cell lines in vitro and in vivo [ 56 ]. Application of GSK-650394 to attenuates breast cancer lung metastasis in mice [ 57 ], and we wondered whether GSK-650394 had similar efficacy in CRLM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GSK-650394 has been validated in in vitro models to attenuate cerebral ischemia-reperfusion injury. [ 31 33 ] Related studies have shown that GSK-650394 exhibits antitumor activity in established breast cancer cell lines in vitro and in vivo [ 56 ]. Application of GSK-650394 to attenuates breast cancer lung metastasis in mice [ 57 ], and we wondered whether GSK-650394 had similar efficacy in CRLM.…”
Section: Resultsmentioning
confidence: 99%
“…In a mouse model, administration of an SGK1 inhibitor (GSK-650394) reduced cerebral ischemia–reperfusion injury [ 31 , 32 ]. In a rat model of global cerebral ischemia, administration of GSK-650394 was noted to improve the learning and memory deficits caused by cerebral ischemia in rats [ 33 ]. SGK1 plays an important role in tumorigenesis, proliferation, apoptosis, invasion, metastasis and autophagy processes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Y-maze test can evaluate spatial memory quantitatively and objectively. Studies have shown that in the Y-maze test, the spontaneous alternation rate decreased in rats’ post-resuscitation, suggesting cognitive impairment ( Lee et al, 2020 ). Electrical stimulation is needed in Y-maze test, which will cause stress to rats.…”
Section: Neurologic Deficit Assessmentmentioning
confidence: 99%
“…52 GSK-650394 has been validated in in vitro models to attenuate cerebral ischemia-reperfusion injury. [31][32][33] Related studies have shown that GSK-650394 exhibits antitumor activity in established breast cancer cell lines in vitro and in vivo. 53 Application of GSK-650394 to attenuates breast cancer lung metastasis in mice, 54 and we wondered whether GSK-650394 had similar e cacy in CRLM.…”
Section: Gsk-650394 Regulates Nets Formation In Crlm Mice With Ir Bac...mentioning
confidence: 99%
“…31,32 In a rat model of global cerebral ischemia, administration of GSK-650394 was noted to improve the learning and memory de cits caused by cerebral ischemia in rats. 33 SGK1 plays an important role in tumorigenesis, proliferation, apoptosis, invasion, metastasis and autophagy processes. 30 In mouse models, activation of neutrophil SGK1 promotes ROS production and NETs formation.…”
Section: Introductionmentioning
confidence: 99%